THREE-DIMENSIONAL (3D) PRINTED COMPOSITE INLAYS AND ONLAYS: FIT ACCURACY, MECHANICAL BEHAVIOR, AND POST-PROCESSING VARIABLES: A NARRATIVE REVIEW - Karolina Buć,; Łukasz Krzystek,; Paweł Buć,; Jagoda Józefczyk,; Konrad Zieliński,; Karolina Ganczar,; Michał Mazurek,; Marianna Rudzińska,; Mikołaj Zalewski,; Stanisław Jurkowski, (International Journal of Innovative Technologies in Social Science, 2025)
Recent advances in three-dimensional (3D) printing have introduced permanent photopolymer resins as potential alternatives for indirect restorative applications. This narrative review evaluated studies published between 2018 and 2025 that investigated the internal and marginal fit, mechanical performance, and post-processing parameters of 3D-printed permanent composite inlays and onlays. Data were obtained from PubMed using keywords related to 3D printing, dental resin composites, inlay, and onlay. Both in vitro and experimental studies were included without language restriction. The majority of included studies demonstrated clinically acceptable adaptation values for 3D-printed restorations, often comparable or superior to milled equivalents. However, fracture resistance and long-term stability remained less consistent, primarily due to variability in post-curing and polymer network maturation. Within current limitations, 3D-printed permanent composites present promising potential for indirect posterior restorations, yet milling continues to represent the clinical gold standard until post-processing and material standardization are achieved.